Pedal cadence does not affect muscle damage to eccentric cycling performed at similar mechanical work - Ueda, Hisashi; Saegusa, Riki; Tsuchiya, Yosuke; Ochi, Eisuke (Frontiers in Physiology, 2023)
Purpose: This study aimed to investigate muscle damage when performing equal mechanical work of fast and slow pedaling speed by eccentric muscle actions (ECCs) cycling. Methods: Nineteen young men [mean ± standard deviation (SD) age: 21.0 ± 2.2 years; height: 172.7 ± 5.9 cm; and body mass: 70.2 ± 10.5 kg] performed maximal effort of ECCs cycling exercise with fast speed (Fast) and slow speed trials (Slow). First, subjects performed the Fast for 5 min by one leg. Second, Slow performed until the total mechanical work was equal to that generated during Fast other one leg. Changes in maximal voluntary isometric contraction (MVC) torque of knee extension, isokinetic pedaling peak torque (IPT), range of motion (ROM), muscle soreness, thigh circumference, muscle echo intensity, and muscle stiffness were assessed before exercise, and immediately after exercise, and 1 and 4 days after exercise. Results: Exercise time was observed in the Slow (1422.0 ± 330.0 s) longer than Fast (300.0 ± 0.0 s). However, a significant difference was not observed in total work (Fast:214.8 ± 42.4 J/kg, Slow: 214.3 ± 42.2 J/kg). A significant interaction effect was not observed in peak values of MVC torque (Fast:1.7 ± 0.4 Nm/kg, Slow: 1.8 ± 0.5 Nm/kg), IPT, muscle soreness (Fast:4.3 ± 1.6 cm, Slow: 4.7 ± 2.9 cm). In addition, ROM, circumference, muscle thickness, muscle echo intensity, and muscle stiffness also showed no significant interaction. Conclusion: The magnitude of muscle damage is similar for ECCs cycling with equal work regardless of velocity.